2017
DOI: 10.18632/oncotarget.18766
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the correlation between vitamin D and lung cancer risk and outcomes

Abstract: In this meta-analysis, we analyzed the association between vitamin D levels and lung carcinoma risk and outcomes. Two authors independently searched the Web of Science, Pubmed, EBSCO and Ovid MEDLINE resources with the key words “vitamin D, lung cancer, solar and latitude” and enrolled 22 studies that satisfied the inclusion criteria. The summary odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using the random (or fixed)-effects model. Potential confounders were carefully adjusted. High v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 85 publications
3
57
2
6
Order By: Relevance
“…Se ha asociado a la vitamina D diversos efectos, entre los que destaca su acción sobre la protección de la salud ósea, hipertensión, diabetes tipo II, niveles de colesterol, anticancerígeno, inmunoestimulador, potenciador en la absorción de calcio y fosfato entre otros 3,4,5,6,27,28,29,30,31,32 .…”
Section: Vitamina Dunclassified
See 1 more Smart Citation
“…Se ha asociado a la vitamina D diversos efectos, entre los que destaca su acción sobre la protección de la salud ósea, hipertensión, diabetes tipo II, niveles de colesterol, anticancerígeno, inmunoestimulador, potenciador en la absorción de calcio y fosfato entre otros 3,4,5,6,27,28,29,30,31,32 .…”
Section: Vitamina Dunclassified
“…También se ha asociado a bajos niveles séricos de vitamina D con enfermedades inmunológicas, riesgo cardiovascular, cáncer, diabetes tipo II entre otras patologías 3,4,5,6,27,28,51,52,53 (Tabla 1). Hipervitaminosis D La gran mayoría de los casos de hipervitaminosis D son producto de una sobre suplementación dietética, la hipervitaminosis D se asocia principalmente a una hiperestimulación de la hormona paratiroidea y una hipercalcemia sanguínea, este exceso de calcio causa alteraciones del ritmo cardiaco, estados de confusión y desorientación.…”
Section: Hipovitaminosis Dunclassified
“…Three single nucleotide polymorphisms (rs2282679 (GC), rs12785878 (NADSYN1/DHCR7), rs10741657 (CYP2R1)), located in or near the genes for vitamin D synthesis and metabolism and identified from two previous genome-wide association studies [21,22] were used to create allele scores. In contrast to two recent meta-analyses [23,24] of non-Mendelian randomisation studies, SUN et al [20] reported no significant association between the vitamin D increasing alleles of rs2282679, rs12785878, rs10741657 and the overall risk of lung cancer incidence or any of the three histologic types, refuting the causal association suggested previously. In one of the meta-analyses [23] a 28% reduced risk for overall lung cancer and further reduction in risk for higher 25(OH)D levels was reported but there was no significant role on survival.…”
mentioning
confidence: 77%
“…In contrast to two recent meta-analyses [23,24] of non-Mendelian randomisation studies, SUN et al [20] reported no significant association between the vitamin D increasing alleles of rs2282679, rs12785878, rs10741657 and the overall risk of lung cancer incidence or any of the three histologic types, refuting the causal association suggested previously. In one of the meta-analyses [23] a 28% reduced risk for overall lung cancer and further reduction in risk for higher 25(OH)D levels was reported but there was no significant role on survival. On closer scrutiny, only two out of eight studies that were included for calculating the pooled effect size for overall lung cancer had reported significant risk reduction.…”
mentioning
confidence: 77%
“…However, this meta-analysis found no relationship between high vitamin D supplementation and a reduction in the risk of NSCLC. In a meta-analysis by Liu et al [15] reported that vitaminD-fortified diet significantly reduced the risk of NSCLC and higher serum vitamin D level significantly reduced NSCLC-related mortality. In a meta-analysis by Muller et al [16] involving 20 prospective cohort studies, patients with lung cancer, serum vitamin D levels measured five years before the diagnosis of NSCLC did not differ from those of age, sex, blood test date, race, and smoking status-matched controls and the authors reported no relationship between serum vitamin D concentration and the risk of developing lung cancer.…”
Section: Discussionmentioning
confidence: 99%